1998
DOI: 10.1073/pnas.95.4.1770
|View full text |Cite
|
Sign up to set email alerts
|

From differentiation to proliferation: The secretory amyloid precursor protein as a local mediator of growth in thyroid epithelial cells

Abstract: In various species, thyrotropin (TSH) is known to stimulate both differentiation and proliferation of thyroid follicle cells. This cell type has also been shown to express members of the Alzheimer amyloid precursor (APP) protein family and to release the secretory N-terminal domain of APP (sAPP) in a TSH-dependent fashion. In this study on binding to the cell surfaces, exogenously added recombinant sAPP stimulated phosphorylation mediated by mitogenactivated protein kinase and effectively evoked proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 34 publications
4
81
0
3
Order By: Relevance
“…Gain-of-function studies showed that APP overexpression leads to increased cellular proliferation (12,17,42). Lossof-function studies either by APP knockdown (14,16,17) or blockage of sAPP function by antibody application (15) demonstrated regression of carcinoma growth in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gain-of-function studies showed that APP overexpression leads to increased cellular proliferation (12,17,42). Lossof-function studies either by APP knockdown (14,16,17) or blockage of sAPP function by antibody application (15) demonstrated regression of carcinoma growth in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These results clearly indicate that the secreted N-terminal domain of APP plays an essential regulatory role in promoting cellular growth. Several lines of evidence showed that sAPP␣ fulfills criteria of a trophic growth factor (42,45,(57)(58)(59) and that the growth regulating activity of APP is specified to the N-terminal domain of sAPP containing the 5-amino acid sequence RERMS (APP-(328 -332)). Peptides containing this pentapeptide sequence could increase cellular proliferation in fibroblasts and induce FIGURE 6.…”
Section: ␤-Amyloid Precursor Protein Is a Tumor Growth Factormentioning
confidence: 99%
“…Therefore, APP can influence the cellular growth not only via its trophic domain amino acids sequence but also via a mechanism that is still undefined at present. The sAPP has been reported to activate ERKs in a Rasdependent fashion, 7,10 and an amino-terminal region of sAPP, which is distinct from the trophic domain mentioned above, is responsible for this effect, though the precise underlying mechanisms for sAPP internalization and/or interaction of sAPP with ERKs signaling pathway are largely uncertain. 10,11 In accordance with these observations, overexpression of APP in neuroectodermal cells resulted in a steady-state hyperactivation of ERK2.…”
Section: Reduced Tumor Growth Of App Antisense Clones In Nude Micementioning
confidence: 99%
“…Given the previous observations that APP could have an important role in the growth of fibroblasts and certain epithelial cells, 6,7 it is reasonable to postulate that APP has a crucial role in the cellular growth and survival of not only neural cells 1 but also non-neural cells including carcinoma cells. Understanding the mechanism underlying the effect of APP on the growth of carcinoma cells would also shed light on the undetermined physiological function of this ubiquitous protein in nonneural cells.…”
Section: Reduced Tumor Growth Of App Antisense Clones In Nude Micementioning
confidence: 99%
See 1 more Smart Citation